Factors of the policy process influencing Health in All Policies in local government: A scoping review - Lilly, Kara; Kean, Bridie; Hallett, Jonathan; Robinson, Suzanne; Selvey, Linda A. (Frontiers in Public Health, 2023)
Objectives: This review aimed to identify factors in the policymaking environment that influence a Health in all Policies approach in local government, how these vary across different municipal contexts, and the extent that theories of the policy process are applied. Methods: A scoping review was conducted to include sources published in English, between 2001-2021 in three databases, and assessed for inclusion by two blind reviewers. Results: Sixty-four sources were included. Sixteen factors of the policy process were identified, expanding on previously reported literature to include understanding and framing of health, use of evidence, policy priority, and influence of political ideology. Eleven sources applied or referred to theories of the policy process and few reported findings based on different local government contexts. Conclusion: There are a range of factors influencing a Health in All Policies approach in local government, although a limited understanding of how these differ across contexts. A theory-informed lens contributed to identifying a breadth of factors, although lack of explicit application of theories of the policy process in studies makes it difficult to ascertain meaningful synthesis of the interconnectedness of these factors.